2010
DOI: 10.1007/s10803-010-0935-9
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorders in Gender Dysphoric Children and Adolescents

Abstract: Only case reports have described the co-occurrence of gender identity disorder (GID) and autism spectrum disorders (ASD). This study examined this co-occurrence using a systematic approach. Children and adolescents (115 boys and 89 girls, mean age 10.8, SD = 3.58) referred to a gender identity clinic received a standardized assessment during which a GID diagnosis was made and ASD suspected cases were identified. The Dutch version of the Diagnostic Interview for Social and Communication Disorders (10th rev., DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
251
2
19

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 403 publications
(287 citation statements)
references
References 22 publications
(32 reference statements)
15
251
2
19
Order By: Relevance
“…Authors investigating rates of ASD in trans people attending services have found that up to 7.8% of them report a lifetime prevalence of ASD [12]. However, these findings are contradictory to more recent studies which have shown no differences between trans people and the general population in relation to ASD [16].…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Authors investigating rates of ASD in trans people attending services have found that up to 7.8% of them report a lifetime prevalence of ASD [12]. However, these findings are contradictory to more recent studies which have shown no differences between trans people and the general population in relation to ASD [16].…”
Section: Introductionmentioning
confidence: 86%
“…Out of the 19 articles, eight were case reports [13,21,22,23,24,25,26,27] and four were cohort studies. The first cohort study explored the development of gender identity in children with Autism [28], the second established the co-occurrence of ASD and Gender Dysphoria [12], the third attempting to establish predictive factors for autism spectrum traits [29], and the fourth reviewed the overrepresentation of adolescent developmental problems in minors with Gender Dysphoria [30]. Six studies considered within this systematic review were case control studies, two of which employed the AQ to compare autism spectrum traits within a sample of patients with Gender Dysphoria and a control group [16,31].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations